Analysis Of Traffic Accident Area On The Road In Gresik District Based On Geographic Information System - Choirul Umam, Mohammad Wildan; Hardaningrum, Farida; Durrotun Nasihien, Ronny (Malikussaleh University, Aceh, Indonesia, 2021)
Gresik regency as the population increases and people use roads for their activities, accidents often occur on roads, especially in Manyar sub-district, which also has many industrial places. According to accident data for the last 4 years from the police, it was found that there was an increase and decrease in the number of accident events each year. This study uses secondary data from the local police. Then the data is analyzed using the EAN (Equivalent Accident Number), UCL (Upper Control Limit), BKA (Upper Control Limit) method, and using QGIS software to display in more detail the accident-prone areas. The results of the analysis using the EAN method obtained the highest number of accidents on Jl. Raya Manyar KM 10 is 604. For the BKA value of 384, while the UCL value is 374, from these results that the EAN value at JL Raya Manyar KM 10 exceeds the BKA and UCL values, it can be concluded that Jl. Raya Manyar KM 10 is an accident-prone area. The results of the analysis are then entered into the QGIS software to display in more detail the areas prone to traffic accidents on roads in Manyar District, Gresik.